2000
DOI: 10.1111/j.1349-7006.2000.tb00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Distribution of TA02, Which is Homologous with a New Type of Aspartic Proteinase, Napsin A

Abstract: The N-terminal amino acid sequence of TA02 (molecular weight 35.0 kDa, isoelectric point 5.29), which is associated with primary lung adenocarcinoma, was determined and a fragment peptide was used to generate mouse monoclonal antibodies (mAbs) against TA02. The amino acid sequence suggested that TA02 might be homologous with napsin A, a new type of aspartic proteinase. In this context, we confirmed the expression of napsin A in primary lung adenocarcinoma using reversetranscription polymerare chain reaction (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 11 publications
3
56
2
Order By: Relevance
“…High cytosolic cathepsin D levels are associated with poor prognosis in primary breast cancer (Foekens et al, 1999). Although we did not find an association between napsin expression and patients' prognosis in this study (data not shown), a correlation between napsin expression and the differentiation grade of adenocarcinoma was observed in accordance with previous reports (Hirano et al, 1997(Hirano et al, , 2000. The high positive rate (more than 80%) of napsin in lung adenocarcinoma and its close association with the differentiation grade may suggest a role of napsin in cancer development or differentiation.…”
Section: Napsin In Lung Cancersupporting
confidence: 74%
See 1 more Smart Citation
“…High cytosolic cathepsin D levels are associated with poor prognosis in primary breast cancer (Foekens et al, 1999). Although we did not find an association between napsin expression and patients' prognosis in this study (data not shown), a correlation between napsin expression and the differentiation grade of adenocarcinoma was observed in accordance with previous reports (Hirano et al, 1997(Hirano et al, , 2000. The high positive rate (more than 80%) of napsin in lung adenocarcinoma and its close association with the differentiation grade may suggest a role of napsin in cancer development or differentiation.…”
Section: Napsin In Lung Cancersupporting
confidence: 74%
“…Our group and another group have shown that napsin A is identical to the protein spots TAO1/TAO2 detected by two-dimensional gel electrophoresis of lung adenocarcinoma, and that napsin A is expressed in type II pneumocytes and lung adenocarcinomas (Chuman et al, 1999;Hirano et al, 2000). However, the detailed expression patterns of napsin A in association with other markers in lung cancer remain to be clarified.…”
mentioning
confidence: 95%
“…[1][2][3][4] Napsin A has a role in processing pulmonary surfactant B protein produced by alveolar type II pneumocytes; 5,6 thus, it has been reported to be a good diagnostic marker for the confirmation of primary lung adenocarcinoma together with thyroid transcription factor 1 (TTF-1). [7][8][9][10][11][12][13] Expression of napsin A is also observed in the fetal kidney 14 and proximal tubules of the adult kidney, where it is most likely involved in protein catabolism.…”
mentioning
confidence: 99%
“…We have applied this methodology to clinical materials of solid malignant neoplasm since 1992. [6][7][8] We detected some polypeptides related to drug resistance comparing 2-DE patterns of parent strains of lung cancer cultured cells with the CDDPresistant strains. We investigated the relationship between the expression of these polypeptides and its clinically postoperative effects of patients with NSCLC.…”
mentioning
confidence: 99%